Immunomodulatory effect of Morinda citrifolia and Andrographis paniculata on expression of toll-like receptors in Nicobari fowl - SUNDER, JAI; SUJATHA, T; RAJA, A; KUNDU, A (The Indian Journal of Animal Sciences, 2016)
This study was conducted to observe the effects of dietary noni and kalmegh supplementation on production performance, immunity and gene expression of toll-like receptors in Nicobari fowl. Supplementation of noni and kalmegh significantly influenced the gene expression levels of TLR-2, TLR-3, TLR-4, TLR-5, TLR-15 and TLR-21 as compared to control. The selectively increased TLR-3, TLR- 4 and TLR-5 and decreased expression of TLR-7 indicated that supplementing noni fruit and kalmegh (@ 10 ml + 200 mg / day / bird) induces antiviral and antibacterial responses in chicken. In conclusion, noni and kalmegh might be promising alternatives for antibiotic growth promoters and commercial immune boosters to improve the production of safety poultry produce.